2015
DOI: 10.1186/s12967-015-0589-7
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase as a novel regulator of 17β-estradiol-induced cell growth through a control of the estrogen receptor/IGF-1 receptor/PDZK1 axis

Abstract: BackgroundWe and others have extensively investigated the role of PARP-1 in cell growth and demise in response to pathophysiological cues. Most of the clinical trials on PARP inhibitors are targeting primarily estrogen receptor (ER) negative cancers with BRCA-deficiency. It is surprising that the role of the enzyme has yet to be investigated in ER-mediated cell growth. It is noteworthy that ER is expressed in the majority of breast cancers. We recently showed that the scaffolding protein PDZK1 is critical for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…MCF-7 cells had been already treated with olaparib in earlier studies and three different doses were tested (2.5, 5 and 10 µM) 64 . Recent data suggested that PARP inhibitors might be useful to treat estrogen receptor-positive and estrogen-dependent tumors 65 . Here we could show that targeting PARP1/2 with olaparib did not alter the 3D aggregation of the MCF-7 cells cultured on the RPM, which indicated that PARP seems not to be the main key factor responsible for 3D spheroids formation in simulated microgravity.…”
Section: Discussionmentioning
confidence: 99%
“…MCF-7 cells had been already treated with olaparib in earlier studies and three different doses were tested (2.5, 5 and 10 µM) 64 . Recent data suggested that PARP inhibitors might be useful to treat estrogen receptor-positive and estrogen-dependent tumors 65 . Here we could show that targeting PARP1/2 with olaparib did not alter the 3D aggregation of the MCF-7 cells cultured on the RPM, which indicated that PARP seems not to be the main key factor responsible for 3D spheroids formation in simulated microgravity.…”
Section: Discussionmentioning
confidence: 99%
“…BCL2 is an anti-apoptotic protein and plays an oncogenic role in MCF-7 cancer cells [32]. Earlier reports suggest that estrogenic signalling regulates BCL2 on direct interaction at the coding region; whereas, it regulates PARP via IGF-1/PDZK axis in breast cancer cells [33,34]. So this made BCL2 and PARP an interesting choice for investigation on the induction of apoptosis in the context of ZRF1, as it is also regulated by estrogenic signalling.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that PARP1 regulates estrogen-dependent breast cancer cell growth through the modulation of the estrogen receptor (ER)-insulin-like growth factor 1 receptor (IGF-1R)-Na(+)/H(+) exchange regulatory cofactor NHE-RF3 (PDZK1) axis. Thus, PARP inhibitors may be powerful weapons for the therapy of ER-positive cancers (Kim et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%